FAKTOR-FAKTOR KEPUTUSAN PEMBELIAN PEMPEK DI PASAR ATAS BATURAJA KECAMATAN BATURAJA TIMUR KABUPATEN OGAN KOMERING ULU - Safitri, Umi; Ogari, Putri Ayu; Gribaldi, Gribaldi (Universitas Galuh, 2023)
The formulation of the problem in this study is what factors influence the decision to buy pempek in the Baturaja market. So the author wants to examine more deeply about the factors that influence the decision to continue buying pempek in the Baturaja market. The purpose of this research is to analyze the factors that influence the decision to buy pempek in the upper market. The research method used is survey method. The number of population in this study is not known with certainty. Sampling in this study was using